Effectiveness of partially purified Bacillus spp. bacteriocins in controlling the growth of LactoBacillus plantarum in soybean curd and Listeria monocytogenes in an edible cricket - Ananchaipattana, Chiraporn; Okamoto, Susumu; Inatsu, Yasuhiro (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2024)
Although some Bacillus (B.) species have been reported to produce bacteriocins, their study and application are limited. In this study, we partially purified and characterized bacteriocins from two Bacillus strains isolated from Thai fermented soybeans. Then, we evaluated the effectiveness of one of the bacteriocins in controlling the growth of a Gram-positive spoilage bacterium (LactoBacillus plantarum) in soybean curd (tofu) and a pathogen (Listeria monocytogenes) in an edible cricket. In five candidate Bacillus strains, one B. subtilis strain (T8434) and one B. velezensis (T8448) strain produced heat-resistant bacteriocins that were effective in controlling the growth of several Gram-positive bacteria. Partially purified bacteriocins produced by these strains were heat stable (95 °C for 10 min), were sensitive to proteinase K digestion, harbored a negative charge at neutral pH, and were smaller than 10 kDa in molecular mass. The bacteriocins suppressed the growth of inoculated spoilage lactic acid bacteria (LAB), which is LactoBacillus plantarum in soybean curd (tofu) and inoculated pathogenic Gram-positive bacteria (Listeria monocytogenes) in the edible cricket for 7 and 2 days at 10 °C, respectively. The Bacillus bacteriocins were considered to have the potential to control the growth of Gram-positive spoilage and pathogenic bacteria in solid foods.